Changing Parental Nutrition Administration Sets Every 24 h versus Every 48 h in Newborn Infants - Miriam Fox; Marion Molesky; John E Van Aerde; Sarah Muttitt (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine whether changing total parenteral nutrition fluid administration sets (TAS) every 48 h rather than every 24 h results in a greater infusate contamination rate.